a) $\frac{2}{3}$ + $\frac{5}{3}$.x= $\frac{5}{7}$ b) $\frac{1}{2}$ (x- $\frac{1}{3}$ ) + $\frac{-1}{2}$ = $\frac{3}{4}$

Question

a) $\frac{2}{3}$ + $\frac{5}{3}$.x= $\frac{5}{7}$
b) $\frac{1}{2}$ (x- $\frac{1}{3}$ ) + $\frac{-1}{2}$ = $\frac{3}{4}$

in progress 0
Liliana 3 tháng 2021-09-10T03:13:55+00:00 2 Answers 7 views 0

Answers ( )

    0
    2021-09-10T03:14:59+00:00

    a) `2/3 + 5/3 .x = 5/7`

    `5/3 . x = 5/7 – 2/3`

    `5/3 .x = 1/21`

    `x = 1/21 : 5/3`

    `x=  1/35`

    b) `1/2 (x-1/3) + (-1)/2 = 3/4`

    `1/2 (x-1/3) = 3/4 – (-1)/2`

    `1/2 (x-1/3) = 5/4`

    `x-1/3 = 5/4 : 1/2`

    `x-1/3 = 5/2`

    `x= 5/2 + 1/3`

    `x= 17/6`

    0
    2021-09-10T03:15:35+00:00

    a, $\frac{2}{3}$ + $\frac{5}{3}$ .x= $\frac{5}{7}$ 

    $\frac{5}{3}$.x= $\frac{5}{7}$ + $\frac{2}{3}$ 

    $\frac{5}{3}$ .x= $\frac{1}{21}$ 

        x = $\frac{1}{21}$ :  $\frac{5}{3}$  

        x= $\frac{1}{35}$ 

    Vậy x= $\frac{1}{35}$ 

    b,  $\frac{1}{2}$ .(x- $\frac{1}{3}$ )+ $\frac{-1}{2}$ = $\frac{3}{4}$ 

         $\frac{1}{2}$ .(x- $\frac{1}{3}$ )           = $\frac{3}{4}$ – $\frac{-1}{2}$

         $\frac{1}{2}$ .(x- $\frac{1}{3}$ )           =$\frac{5}{4}$

               x-$\frac{1}{3}$               =$\frac{5}{4}$:$\frac{1}{2}$

               x-$\frac{1}{3}$             =       $\frac{5}{2}$

                x                                     = $\frac{5}{2}$+$\frac{1}{3}$

                x                                      =            $\frac{17}{6}$

    Vậy x= $\frac{17}{6}$

    CHÚC BẠN HỌC TỐT!!!

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )